2023
DOI: 10.1007/s40121-023-00775-4
|View full text |Cite
|
Sign up to set email alerts
|

Causal Associations Between Tobacco, Alcohol Use and Risk of Infectious Diseases: A Mendelian Randomization Study

Abstract: Introduction:The causal effects of smoking and alcohol use on the risk of infectious diseases are unclear, and it is hard investigate them in an observational study due to the potential confounding factors. The aim of this study was to use Mendelian randomization (MR) techniques to assess the causalities between smoking, alcohol use and risk of infectious diseases. Methods: Univariable and multivariable MR analyses were performed using genome-wide association data for the age of initiation of regular smoking (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…To examine if the potential genetic tools related to micronutrients were linked to other traits like blood metabolites (Wei et al, 2023), BMI (Wang et al, 2023), insomnia (Thorkildsen et al, 2023), and lifetime smoking (Zhu et al, 2023), we employed PhenoScanner V2. The website http//www.phenoscanner.medschl.cam.ac.uk/ was accessed on 1 November 2023.…”
Section: Mr Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…To examine if the potential genetic tools related to micronutrients were linked to other traits like blood metabolites (Wei et al, 2023), BMI (Wang et al, 2023), insomnia (Thorkildsen et al, 2023), and lifetime smoking (Zhu et al, 2023), we employed PhenoScanner V2. The website http//www.phenoscanner.medschl.cam.ac.uk/ was accessed on 1 November 2023.…”
Section: Mr Analysismentioning
confidence: 99%
“…Although sensitivity analyses did not uncover any indications of bias that would make the MR estimates unreliable, we proceeded to examine the second characteristic linked to the leading SNP for Zn by utilizing the PhenoScanner tool [blood metabolites (Wei et al, 2023), BMI (Wang et al, 2023), insomnia (Thorkildsen et al, 2023), and lifetime smoking (Zhu et al, 2023)]. However, no connections were observed between Zn-related instrumental variables and reported risk factors (Supplementary Table S11).…”
Section: Confounder and Multivariable Mr Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Body mass index (BMI) and smoking are significant confounding factors in the relationship between ADs and sepsis [29][30][31][32] . Therefore, in evaluating the independent causal effects of ADs on susceptibility and the short-term mortality risk from sepsis, we conducted a multivariable Mendelian randomization (MVMP) analysis to adjust for BMI and smoking.…”
Section: Mendelian Randomization Analysesmentioning
confidence: 99%
“…Of these, 31 articles that fulfilled the inclusion criteria were included in the study. The categorization of the included studies by outcome revealed the following: 14 articles related to circulatory system diseases [15][16][17][18][19][20][21], 27 addressing digestive system diseases [22][23][24][25][26][27], 1 concerning mental and behavioral disorders [28], 6 focusing on nervous system diseases [29][30][31][32][33][34], 26 on neoplasms [22,[35][36][37][38][39], 11 on other diseases [33,[40][41][42][43][44][45]. Furthermore, we extended to conducting 151 novel MR analyses, comprising 76 on alcohol consumption and 75 on problematic alcohol use.…”
Section: Literature Search Study Selection and De Novo Mrmentioning
confidence: 99%